The Effect of Training and Development on Employee Performance At Pt. Daewon Electric Indonesia - Askur Wahyudi; Atik Budi Paryanti; Tuti Achyani; Rendy Permana; Selvi Awaliah; Putri Ayu Lestari (Jurnal Mantik, 2022)
This study aims to examine and analyze the effect of training and development on employee performance at PT. Daewon Electric Indonesia. The benefit of this research is to provide information about Training and Development on employee performance at PT. Daewon Electric Indonesia. The population in this study were all employees at PT. Daewon Electric Indonesia, which has 58 employees. The method of data collection in this study is to use a questionnaire. Analysis of the data used in this study is multiple linear regression. The results of this study are simultaneously training and development have a positive and significant effect on employee performance at PT. Daewon Electric Indonesia. Partially, training has a positive and significant effect on employee performance at PT. Daewon Electric Indonesia. Partially the development of human resources has a positive and significant effect on the performance of employees at PT. Daewon Electric Indonesia.